Involvement of Neuropeptide Y within Paraventricular Nucleus in Electroacupuncture Inhibiting Sympathetic Activities in Hypertensive Rats - Qi Zhang; Yingying Tan; Xin Wen; Fangfang Li (International Journal of Hypertension)
Although electroacupuncture (EA) has been used to decrease the blood pressure (BP) clinically, the underlying mechanisms are not clearly clarified. This study aimed to assess the hypothesis that EA treatment exerts a hypotensive action via suppressing sympathetic activities and modulating neuropeptide Y (NPY) function within the paraventricular nucleus (PVN) of hypertensive rats. Male Sprague-Dawley rats were selected for the experiment, and the hypertensive models were established by the two-kidney, one-clip (2K1C) method. Then, the rats were randomly assigned to the sham group, 2K1C group, 2K1C plus EA group, and 2K1C plus sham EA group. EA treatment at the acupoints ST36 and ST40 overlying the peroneal nerves was given once a day for 30 days. The radiotelemetry system was applied to collect the arterial BP recordings. Power spectral analyses of BP variability, BP responses to ganglionic blockade, and plasma levels of norepinephrine and epinephrine were performed to assess the changes in sympathetic nerve activity. Real-time PCR and Western blots were carried out to examine the expression of NPY system in the PVN. The responses of PVN microinjection with NPY Y1R antagonist BIBO3304 were detected to check the endogenous NPY tone. The results showed that the enhanced arterial BP and sympathetic activities were effectively reduced by 30 days of EA treatment, and baroreflex sensitivity was improved in 2K1C hypertensive rats. The level of NPY mRNA and protein expression in the PVN was markedly upregulated by EA treatment in 2K1C rats. In addition, the pressor responses of PVN microinjection with NPY Y1R antagonist BIBO3304 in 2K1C models were remarkably augmented by the EA stimulation. Our results indicate that the increased NPY expression and function in the PVN induced by EA treatment contribute to antihypertensive and sympathetic suppression on hypertensive rats. The findings may elucidate the underlying mechanisms of the acupuncture to be a potential therapeutic strategy against hypertension.